2020
DOI: 10.1007/s12020-020-02295-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different systems of ultrasound (US) risk stratification for malignancy in elderly patients with thyroid nodules. Real world experience

Abstract: Comparison of different systems of (US) risk stratification for malignancy in elderly patients with thyroid nodules. Real world experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…These points should be taken into consideration when current guidelines are updated or in the development of new systems. These results were consistent with data reported by Di Fermo et al [ 15 ], which supported the validity of sonographic stratification systems in elderly patients, even if the specificity of suspicious features, in this setting, was lower than expected. Conversely, in our cohort, there was no significant difference in diagnostic performance between the ATA and AACE/ACE/AME systems.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These points should be taken into consideration when current guidelines are updated or in the development of new systems. These results were consistent with data reported by Di Fermo et al [ 15 ], which supported the validity of sonographic stratification systems in elderly patients, even if the specificity of suspicious features, in this setting, was lower than expected. Conversely, in our cohort, there was no significant difference in diagnostic performance between the ATA and AACE/ACE/AME systems.…”
Section: Discussionsupporting
confidence: 93%
“…Most recently, the ACR TIRADS and the sonographic risk-stratification systems proposed by the American Thyroid Association (ATA) [ 2 ] and the American Association of Clinical Endocrinologists/American College of Endocrinology/Associazione Medici Endocrinologi (AACE/ACE/AME) guidelines [ 1 ] have been validated in a geriatric population [ 15 ]. In that study, it is suggested that age might be a confounder since some suspicious US features of thyroid nodules lack specificity in elderly patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…44 Another cross-sectional study of 1,867 patients with thyroid nodules referred to an academic center for an FNA biopsy (median age, 71 years) comparatively assessed the performance of the ACR-TIRADS, ATA and AACE/ACE/AME classification systems in an older adult population. 43 Overall, the majority of patients had benign cytology (83%) and only 3% had cytology consistent with malignancy. 43 Of 50 malignant nodules, 31 (62%) underwent surgical resection.…”
Section: Thyroid Nodule Evaluationmentioning
confidence: 92%
“…43 Overall, the majority of patients had benign cytology (83%) and only 3% had cytology consistent with malignancy. 43 Of 50 malignant nodules, 31 (62%) underwent surgical resection. The reasons for deferred surgery were not reported.…”
Section: Thyroid Nodule Evaluationmentioning
confidence: 92%
See 1 more Smart Citation